Trends and opportunities in research on disability and work: an interdisciplinary perspective. - Jurado-Caraballo, María Ángeles; Quintana-García, Cristina; Rodríguez-Fernández, María Mercedes (Sage, 2022)
This study aims to analyze status, trends, and possible future research areas in the literature on “disability and work.” It is an in-depth analysis of articles related to this field, published during 1991–2017, in journals included in the Science and Social Sciences Citation Index. Bibliometric methods helped to describe evolution in publications, the most representative contributors, methods applied, main concepts and theories, and topics explored (content analysis). A co-word analysis allowed to create knowledge maps on topics and identify potential venues for future research. The contribution is threefold. First, it contributes to knowledge advancement concerning disability in workplaces, opening new possibilities to discover important research areas. Second, it offers conceptual, theoretical, and methodological suggestions for future research. Third, it has practical implications related to inclusive strategies and initiatives in the workplace which human resource practitioners can use to promote the participation of workers with disabilities improving their labor experience.
Keywords: Personas con discapacidad - Trabajo; Bibliometric methods; Co-word analysis; Disability; Work; Workplace